Person-centered dementia care in home care services - highly recommended but still challenging to obtain: a qualitative interview study - Kari-Anne Hoel; Anne Marie Mork Rokstad; Ingvild Hjorth Feiring; Bjørn Lichtwarck; Geir Selbæk; Sverre Bergh (BMC, 2021)
Abstract Background Dementia is one of the main causes of disability and dependence in older people, and people with dementia need comprehensive healthcare services, preferably in their own homes. A well-organized home care service designed for people with dementia is necessary to meet their needs for health- and social care. Therefore, it is important to gain knowledge about how people with dementia experience the home care service and if the service responds to their wishes and needs. The aim of this study was to explore the experience of home care services among people with dementia, to understand the continuity in services, how the service was adapted to people with dementia, and how the patient experienced person-centered care and shared decision-making. Methods We used a qualitative, exploratory design based on a phenomenological-hermeneutic approach and performed individual in-depth interviews with persons with dementia. A convenience sample of 12 persons with moderate to severe degrees of dementia from four Norwegian municipalities participated in the study. The interviews were conducted in February 2019. Results The findings identified that the participants appreciated the possibility to stay safely in their own homes and mostly experienced good support from staff. They expressed various views and understanding of the service and experienced limited opportunities for user involvement and individualized, tailored service. The overall theme summarizing the findings was: "It is difficult for people with dementia to understand and influence home care services, but the services facilitate the possibility to stay at home and feel safe with support from staff." Conclusion The participants did not fully understand the organization of the care and support they received from the home care services, but they adapted to the service without asking for changes based on their needs or desires. Although person-centered care is recommended both nationally and internationally, the participants experienced little inclusion in defining the service they received, and it was perceived as unclear how they could participate in shared decision-making.